مساهمة القطاع الخاص في الحد من البطالة بولاية سوق أهراس - بلال منايلي; ايمن قرقاح (My University, 2022)
This study aimed to shed light on the importance of the private sector in moving the wheel of économico développement through emplument policies for the workforce and the effective contribution of the private sector to reducing unemployment. This study showed that the private sector in Algeria in general and in general and in soukahras in particular is one of the sectors that depends he has to greatly reduce unemployment, so the state has allocated various forms of financial and material support for its advancement. .......................................................... تهدف هذه الدراسة إلى تسليط الضوء على أحد أهم المواضيع التنموية، والمتمثلة في القطاع الخاص ومساهمته في الحد من البطالة، لكون هذا الأخير حلقة من حلقات الإصلاح الاقتصادي التي يهدف إلى تحسين الوضعية الاجتماعية والاقتصادية للبلاد ولقد بينت هذه الدراسة بان القطاع الخاص في الجزائر بصفة عامة و في ولاية سوق أهراس بصفة خاصة من القطاعات الذي يعول عليه كثيرا في معالجة البطالة حيث خصته الدولة بمختلف أشكال الدعم المالي و المادي للنهوض به.